Dynamic Reconfiguration Systems for PV Plant: Technical and Economic Analysis - Schettino, Giuseppe; Pellitteri, Filippo; Ala, Guido; Miceli, Rosario; Romano, Pietro; Viola, Fabio (Energies (Basel), 2020)
Solar plants suffer of partial shading and mismatch problems. Without considering the generation of hot spots and the resulting security issues, a monitoring system for the health of a PV plant should be useful to drive a dynamic reconfiguration system (DRS) to solve bottlenecks due to different panels’ shading. Over the years different DRS architectures have been proposed, but no suggestions about costs and benefits have been provided. Starting from technical subjects such as differences of the topologies driving the hardware complexity and number of components, this paper identifies the cost of DRS and its lifetime, and based on these issues it provides an economic analysis for a 6 kWp PV plant in different European Union countries, in which the dissimilar incentive policies have been considered.